DAMPAK PENERAPAN PSAK 64 TERHADAP KONSERVATISME PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA - B2091151010, RICKY (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2017)
This study aims to determine the impact of PSAK 64 and other factors which related to the financial reporting conservatism on mining companies in Indonesia. The samples of this research are listed mining companies in Indonesia Stock Exchange from year 2009 to 2010,and from 2013 to 2014. This study uses two exploration models that the first model is analyzing the impact of PSAK 64 implementation and other factors, those are; exploration aggressiveness, managerial ownership, and auditor quality to the financial reporting conservatism. While the second research model is to examine the impact of PSAK 64 implementation to the exploration aggressiveness, managerial ownership, and auditor quality to the financial reporting conservatism. The results of this research on the first model shows that the implementation of PSAK 64, managerial ownership, and auditor quality does not significantly affected to the financial reporting conservatism on mining companies in Indonesia, while exploration aggressiveness mark a notably influence to the financial reporting conservatism on mining companies in Indonesia. Then, for the second research model shows that the implementation of PSAK 64 does not materially affected by the relationship in exploration aggressiveness, managerial ownership, and auditor quality to the financial reporting conservatism on mining companies in Indonesia. The implementation of PSAK 64 does not give a remarkable effect for conservatism because there is no notable difference nor alterability of the financial reporting on mining companies in Indonesia before and after the implementation. Keywords : PSAK 64, conservatism, exploration aggressiveness, managerial ownership, auditor quality